2012
DOI: 10.5670/oceanog.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Chemoautotrophy at Deep-Sea Vents: Past, Present, and Future

Abstract: o C e a N i C S P r e a D i N g C e N t e r P r o C e S S e S | ridge 2000 P r o g r a M r e S e a r C h is currently a notable lack of process-oriented studies that would allow an assessment of the larger role of these ecosystems in global biogeochemical cycles. By combining the presently available powerful "omic" and single-cell tools with thermodynamic modeling, experimental approaches, and new in situ instrumentation to measure rates and concentrations, it is now possible to bring our understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
169
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 26 publications
6
169
0
1
Order By: Relevance
“…On the EPR, within 5 years of each eruption, rapid and sequential colonizations were observed from white bacterial mats, to the small siboglinid tubeworm Tevnia jerichonana, to the giant tubeworm Riftia pachyptila, and to the mussel Bathymodiolus thermophilus (Shank et al, 1998;Fornari et al, 2012). The transition from Tevnia to Riftia appears to correspond to waning vent fluid flux but may also be influenced by biogenic settlement cues (Mullineaux et al, 2000;Sievert and Vetriani, 2012). The mussels are slower to get established, but once they reach adult size and high densities, may reduce the hydrogen sulfide available for tubeworms.…”
Section: Regional and Local Influences On Successionmentioning
confidence: 99%
“…On the EPR, within 5 years of each eruption, rapid and sequential colonizations were observed from white bacterial mats, to the small siboglinid tubeworm Tevnia jerichonana, to the giant tubeworm Riftia pachyptila, and to the mussel Bathymodiolus thermophilus (Shank et al, 1998;Fornari et al, 2012). The transition from Tevnia to Riftia appears to correspond to waning vent fluid flux but may also be influenced by biogenic settlement cues (Mullineaux et al, 2000;Sievert and Vetriani, 2012). The mussels are slower to get established, but once they reach adult size and high densities, may reduce the hydrogen sulfide available for tubeworms.…”
Section: Regional and Local Influences On Successionmentioning
confidence: 99%
“…This work was soon followed by many other pure cultures (Nakagawa and Takai, 2008;Sievert and Vetriani, 2012, and references therein), and represented a major breakthrough as it permitted the genetic and physiological characterization of these organisms. More recently, meta-'omics' studies have shown that the same chemosynthetic pathways described in pure cultures are active in situ (Urich et al, 2014;Fortunato and Huber, 2016).…”
Section: The Discovery Of Chemoautotrophicmentioning
confidence: 99%
“…However, most vent isolates to date appear to be obligate autotrophs, with the exception of the thermophilic genus Nautilia. For N. profundicola and N. lithotrophica, formate is used as an electron donor, N. nitratireducens can use complex organics (Sievert and Vetriani, 2012, and references therein), and natural populations of Nautilia can assimilate acetate (Winkel et al, 2014). Mesophilic, heterotrophic Epsilonproteobacteria have not yet been isolated from vent systems.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations